INNOVATIVE SOLUTIONS FOR SUSTAINABLE LOCAL GOVERNANCE BEST PRACTICES AND IMPACT IN INDONESIAN REGIONS - Sundah, Daisy Iriany Erny; Hidayat, Wahyu; Muhdiarta, Untung; Yanuarisa, Yesika; Anangkota, Muliadi (Alqaprint Jatinangor, 2024)
Sustainable local governance is pivotal for the socio-economic development and environmental resilience of regions. In Indonesia, the quest for effective and sustainable governance faces numerous challenges, including resource constraints, diverse cultural contexts, and varying levels of institutional capacity. This study aims to identify and analyze innovative solutions that have been successfully implemented in various Indonesian regions to promote sustainable local governance. Employing a comprehensive literature review methodology, the research synthesizes data from academic articles, government reports, and case studies. The findings highlight a range of best practices, such as community-based resource management, digital governance platforms, and participatory budgeting processes. These practices have demonstrated significant positive impacts on governance efficiency, community engagement, and sustainable development outcomes. The study also identifies key challenges, such as scalability and adaptability of these innovations across different regions. By addressing these challenges and leveraging the identified best practices, policymakers and local governments can enhance governance sustainability and resilience. This research contributes to the broader discourse on sustainable governance by providing actionable insights and policy recommendations that can be adapted and implemented in similar contexts globally.